Graphene-Based Materials for the Removal of Volatile Organic Compounds - Tao, Huiting; Mei, Tao; Cheng, Hairong (Recent Innovations in Chemical Engineering, 2022)
Volatile organic compounds (VOCs) are a group of organic compounds such as aromatic, aliphatic and chlorinated hydrocarbons, etc. VOCs are emitted into the atmosphere during the production of adhesives, paints, printing materials, building materials, and their use. Although several removal approaches have been employed to remove VOCs, researchers have not stopped exploring new methods and materials for VOCs treatment. Graphene has recently attracted enormous attention for fundamental research and potential applications due to its large specific surface area, high mechanical strength and flexibility, and good chemical and thermal stability. Here we briefly describe the recent progress in graphene-based materials (GBMs) for applications in VOCs removal. GBMs have been exploited as novel materials in VOC adsorption, membrane separation, and photocatalysis. Although the issues need to be further studied, such as biocompatibility, toxicity, and production at low cost, GBMs are promising for VOC removal, which is the current trends and future perspectives of the field. This mini-review represents the potential of GBMs for VOC treatment.
Keywords: graphene